The Effect of Counseling on the Ability of Caring for the Umbilical Cord at The Primigravida Nifas Mother in BPM Nihayatur Rohmah Karangsono Village Kanigoro Blitar Regency - Maria Ulfa; Andestia Imanita (STIKes Patria Husada Blitar, 2017)
The high infant mortality rate due to improper umbilical cord care is increasing. Improper umbilical cord caring behavior is still found in postpartum primigravida, so it is necessary to increase postpartum knowledge of the importance of treating the umbilical cord in the right way to prevent infection. This study design is Quasy-eksperimental one group Pre-post-test-design. Population of this research is Primigravida Nifas Mother one day 2-7 days in BPM Nihayatur Rohmah. The sample in this research is 15 respondents by using total sampling.Data analysis using Wilcoxon test. Results of research on the ability of postpartum primigravida mother in caring for the correct umbilical cord before counseling 6,7% in the able category and after getting counseling there is a 93,3% increase that is 100% in the category capable. Based on the results of the study is expected to respondents more active again in increasing interest by increasing information about caring for the correct umbilical cord to prevent the occurrence of infection